When do People Value Rehabilitation and Restorative Justice Over the Punishment of Offenders?. Issue 1 (2nd January 2019) - Moss, Simon A.; Lee, Eunro; Berman, Alan; Rung, Daile
ABSTRACT: The authors explored the characteristics of individuals that affect their attitudes toward restorative justice-—in which offenders, victims, and communities meet to redress the damage the offence had caused. Across three studies, participants completed questionnaires that assessed whether they believe that people in general, or offenders in particular, can change fundamentally as well as attitudes toward restorative justice, rehabilitation, and punishment. In one study, the questionnaire also included measures of social dominance orientation, goal orientation, and future clarity. Generally, participants who believed that offenders can change fundamentally were more likely to agree to participate in restorative justice meetings and endorse rehabilitation over punishment. Yet, the belief that individuals in general can change fundamentally was not significantly associated with these attitudes toward alternative responses to crime. Social dominance orientation was inversely, and a learning orientation and future clarity were positively, associated with this belief that offenders can change. Thus, interventions that diminish inequality in income, privileges, and influence—and thus curb a social dominance orientation—may foster an openness toward restorative justice. Initiatives that continually reward people who gradually develop their expertise, and thus promote a learning orientation, should also foster this openness toward alternatives to custodial sentences.